SINKRONISASI RENSTRA DINAS PERKEBUNAN DENGAN RPJMD 2019-2023 DAN VISI MISI GUBERNUR KALIMANTAN TIMUR - Abd Rachim AF; Muhammad Habibi (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2020)
The development of plantations in East Kalimantan is directed at strengthening agricultural sector lines as one of the pillars of a sustainable economic structure in East Kalimantan Province. So, there must be synchronization between the programs and activities of the Plantation Service as stated in the strategic plan with the 2019-2023 RPJMD East Kalimantan which is the implementation of the Vision and Mission of the Governor of East Kalimantan. By using a qualitative descriptive approach through literature review or Plantation Service documents, the research results show the Plantation Office has made a Strategic Plan which fully refers to the 2019-2020 RPJMD of the Province of East Kalimantan which is stated and is believed to have contributed greatly to achieving the 2nd and 4th missions in accordance with the Governor's vision and mission. A complete and correct understanding of the Strategic Plan structure of the Plantation Service is the start of the evaluation of the suitability of the contribution to the achievement of the Governor's vision and mission as a basis for evaluating the performance of the agency accompanied by analysis of the most recent and verified data. In 2019 the agricultural sector in a broad sense contributed 7.92% to East Kalimantan's GRDP, namely the plantation sub-sector by 54.80%. The Plantation Office not only contributes to the achievement of the 2nd mission, but directly and indirectly contributes actively in achieving the target of reducing greenhouse gas emissions according to the objectives set in the 4th mission in the 2019-2023 RPJMD.